2000
DOI: 10.1021/es991460z
|View full text |Cite
|
Sign up to set email alerts
|

Sorption Behavior of p-Nitrophenol on the Interface between Anion−Cation Organobentonite and Water

Abstract: A series of anion-cation organobentonite are prepared by incorporating both cationic surfactant bromide dodecyltrimethylammonium (DTMAB) and anionic surfactant sodium dodecyl sulfate (SDS) to bentonite. The results indicate that the organic carbon contents of the organobentonites are proportional to the amounts of anionic and cationic surfactants in bentonite. The amount of organic pollutant removed from water depends greatly on the amount of SDS and DTMAB in the bentonite. Partition and adsorption contributio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
79
0

Year Published

2004
2004
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 134 publications
(82 citation statements)
references
References 33 publications
3
79
0
Order By: Relevance
“…Then, the collected montmorillonite was dried at 105°C, ground in an agate mortar and passed through a 200-mesh sieve. 2 ÁnH 2 O. The surfactants (99% purity) are octadecyl trimethylammonium bromide (C18-S) and octyl trimethylammonium chloride (C8-S), purchased from Nanjing Robiot Co., Ltd., China.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Then, the collected montmorillonite was dried at 105°C, ground in an agate mortar and passed through a 200-mesh sieve. 2 ÁnH 2 O. The surfactants (99% purity) are octadecyl trimethylammonium bromide (C18-S) and octyl trimethylammonium chloride (C8-S), purchased from Nanjing Robiot Co., Ltd., China.…”
Section: Methodsmentioning
confidence: 99%
“…Hence, during the last decades, a number of studies were conducted using different families of clay minerals and surfactants with different configurations to synthesize organoclays [1][2][3][4][5][6][7]. In those studies, most attentions were paid on the thermal properties and the interlayer structure of the obtained organoclays.…”
Section: Introductionmentioning
confidence: 99%
“…Most of the current research efforts in this area focus on organophilic clays which are formed by exchanging the naturally occurring cations, such as Na + , K + , Ca 2+ and Mg 2+ . Zhu et al (2000) indicated that organophilic clays seem to be the most promising option as an adsorbent for organic hazardous waste. Organically-modified clays (organoclays), obtained by exchanging naturally occurring cations (Na + , K + , Ca 2+ , Mg 2+ and etc.)…”
Section: Introductionmentioning
confidence: 99%
“…In the past decades, cationic [11], anionic [12,13], nonionic [14], and amphoteric surfactants [15,16] with various length, and number of the alkyl chains have been used to modify montmorillonite, and the resulting organo-montmorillonites are shown to have quite different structural characteristics [17][18][19]. The material behavior and physical and chemical properties of the corresponding organo-montmorillonites are studied in different research areas [20][21][22][23][24][25], for example, the organoclays with high thermal stability are critical for synthesis and processing of polymer layered silicate nanocomposites.…”
Section: Introductionmentioning
confidence: 99%